PERAN BIMBINGAN PERKAWINAN PRANIKAH DALAM MENCEGAH PERNIKAHAN DINI Studi Kasus Kantor Urusan Agama Kecamatan Sawangan Kabupaten Magelang - Bagas Alfansyah; Triadi Wicaksono (LPPM STAI Muhammadiyah Probolinggo, 2025)
Marriage is an important milestone in family life. However, in Sawangan Subdistrict, Magelang Regency, marriage often occurs at an age below the legal requirement or prior to achieving psychological and biological maturity. The contributing factors include cultural traditions, low levels of education, parental pressure, and limited knowledge of legal and reproductive health issues. This study aims to analyze the role of the Premarital Marriage Guidance Program organized by the Sawangan Office of Religious Affairs (KUA) in preventing early marriage. A qualitative approach with a case study design was employed, using interviews, observations, and documentation. The findings indicate that early marriage is still found in several villages such as Wonolelo, primarily due to social and economic pressures. The Sawangan KUA implements Premarital Marriage Guidance in a structured and collaborative manner in cooperation with community health centers (Puskesmas) and family planning field officers (PLKB), integrating religious, health, and demographic perspectives. The program’s effectiveness is reflected in the significant decrease in applications for marriage dispensation, from 47 cases in 2023 to 23 cases in 2024. This research benefits society by enhancing understanding of the risks of early marriage, thereby encouraging behavioral change toward marriage at an ideal age. For the KUA and related institutions, these findings provide a basis for strengthening premarital guidance programs, developing more relevant educational materials, and expanding cross-sector collaboration to maximize the program’s reach and effectiveness.